The Clock Takes Shape—24 h Dynamics in Genome Topology - Tartour, Kévin; Padmanabhan, Kiran (Frontiers in Cell and Developmental Biology, 2022)
Circadian rhythms orchestrate organismal physiology and behavior in order to anticipate daily changes in the environment. Virtually all cells have an internal rhythm that is synchronized every day by Zeitgebers (environmental cues). The synchrony between clocks within the animal enables the fitness and the health of organisms. Conversely, disruption of rhythms is linked to a variety of disorders: aging, cancer, metabolic diseases, and psychological disorders among others. At the cellular level, mammalian circadian rhythms are built on several layers of complexity. The transcriptional-translational feedback loop (TTFL) was the first to be described in the 90’s. Thereafter oscillations in epigenetic marks highlighted the role of chromatin state in organizing the TTFL. More recently, studies on the 3D organization of the genome suggest that genome topology could be yet another layer of control on cellular circadian rhythms. The dynamic nature of genome topology over a solar day implies that the 3D mammalian genome has to be considered in the 4th dimension- in time. Whether oscillations in genome topology are a consequence of 24hr gene-expression or a driver of transcriptional cycles remains an open question. All said and done, circadian clock-gated phenomena such as gene expression, DNA damage response, cell metabolism and animal behavior – go hand in hand with 24hr rhythms in genome topology.